Moral reasoning through the eyes of persons with behavioral variant frontotemporal dementia - Rea Antoniou; Tobias Hausermann; Alissa Bernstein Sideman; Alissa Bernstein Sideman; Alissa Bernstein Sideman; Alissa Bernstein Sideman; Kristina Celeste Fong; Patrick Callahan; Bruce L. Miller; Bruce L. Miller; Joel H. Kramer; Joel H. Kramer; et al. (Frontiers in Neurology, 2023)
IntroductionPersons with behavioral variant frontotemporal dementia (bvFTD) can exhibit apparently antisocial behaviors. An example is their tendency to adopt utilitarian choices in sacrificial moral dilemmas, i.e. harmful actions to promote overall welfare. Moral cognition models interpret such tendencies as deriving from a lack of emotional engagement and selective impairment in prosocial sentiments.MethodsWe applied a qualitative approach to test those theoretical assumptions and to further explore the emotional experiences and values of people with bvFTD while they contemplate moral scenarios. We conducted semistructured interviews with 14 participants: 7 persons with bvFTD and 7 older healthy controls. Transcripts were coded using ATLAS.ti 5.0.ResultsDuring the moral reasoning task, persons with bvFTD reported more positive emotions than negative and showed significantly less cognitive precision in their moral reasoning compared to controls. Persons with bvFTD also organized their choices predominantly around kindness and altruism, and their responses reflected higher rule compliance. Our study showed that bvFTD persons’ utilitarian responses to moral dilemmas did not arise from an emotionally disengaged or antisocial perspective. Instead, they were underpinned by positive emotionality and prosocial values.DiscussionThese findings enrich current understandings of moral cognition and highlight the importance of incorporating mixed methods approaches in dementia research that take into consideration the viewpoint of cognitively impaired individuals